The Role of Social Studies Learning in Developing Ecocentrism Attitudes of JHS Students in Pontianak - Riama Al Hidayah; Enok Maryani; Dadang Sundawa; Neiny Ratmaningsih (Jurnal PAJAR (Pendidikan dan Pengajaran), 2026)
This study investigates the integration of ecocentrism into the social studies curriculum at SMPN 1 Pontianak City, highlighting the critical role of education in fostering students' environmental awareness. The backdrop of increasing environmental crises, driven by anthropocentric perspectives, necessitates a shift towards ecocentric values that recognize the intrinsic worth of all life forms. Employing a qualitative methodology, including literature reviews and in-depth interviews with educators and students, the research reveals that students exhibit significant environmental consciousness, as evidenced by their proactive efforts to maintain cleanliness and ecological balance in the school environment. Findings indicate that the school's educational approach effectively instils ecocentric principles, promoting a holistic understanding of human-nature interdependence. Furthermore, the curriculum's emphasis on environmental issues cultivates positive attitudes towards sustainability, suggesting that social studies education can serve as a powerful tool for nurturing responsible future citizens. The implications of this research underscore the necessity for educational institutions to prioritise ecological ethics, thereby contributing to the broader discourse on sustainable development and environmental stewardship.